2010
DOI: 10.1002/tax.595006
|View full text |Cite
|
Sign up to set email alerts
|

What we still don't know about polyploidy

Abstract: During the past decade there has been a tremendous resurgence of interest in polyploidy that has in large part been stimulated by the development of increasingly powerful genetic and genomic tools. The result has been numerous new insights into the genomic and genetic consequences of polyploidy. The plethora of new discoveries has dramatically reshaped traditional views and concomitantly revealed that polyploidy is a highly dynamic and ubiquitous process. These recent advances in our understanding of polyploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
325
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(338 citation statements)
references
References 205 publications
(198 reference statements)
3
325
2
Order By: Relevance
“…The BKKK genotypic composition was regarded as a consequence of homeologous recombination during the meiosis of the parents particularly in the synthetic allotetraploid. In some species, homeologous pairing during meiosis is suspected to occur in the first generations following polyploid formation (Ramsey and Schemske, 2002; Soltis et al, 2010; Szadkowski et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BKKK genotypic composition was regarded as a consequence of homeologous recombination during the meiosis of the parents particularly in the synthetic allotetraploid. In some species, homeologous pairing during meiosis is suspected to occur in the first generations following polyploid formation (Ramsey and Schemske, 2002; Soltis et al, 2010; Szadkowski et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Meiotic instabilities are common in interspecific and resynthesized lines (Gaeta et al, 2007; Lyrene, 2016). In some allopolyploid plants, recombination between subgenomes during meiosis was suspected to occur in newly formed polyploids (Ramsey and Schemske, 2002; Soltis et al, 2010) but was rarely observed among stabilized allopolyploids (Salmon et al, 2010; Ainouche and Wendel, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Because broad-scale gene flow is not restricted by geographic segregation of individuals, allopolyploidy clearly represents not only an example of sympatric speciation (Bird et al, 2012), but ''instantaneous'' or ''nearinstantaneous'' speciation (Harrison, 2012Abbott et al, 2013). Consequently, it is regarded as ''the only widely accepted mode of sympatric speciation'' (Hendry, 2009;Soltis et al, 2010). Individual allele sequences derived from N. canadensis (orange), N. muenscheri (pink), or N. canadensis  N. flexilis (green) associated with alleles derived from both N. flexilis (brown) and N. guadalupensis (blue), indicating these taxa to be of hybrid origin (see also Table 6).…”
Section: Najas Canadensis and N Flexilis Arose As Sympatric Speciesmentioning
confidence: 98%
“…The initially increased gene dosage following duplication is often assumed to be beneficial for survival in new habitats, at least in the short term [32]. But although there are certainly polyploid species known for their extreme adaptations to abiotic stresses, an equal fraction are adapted to less harsh conditions, and there are also diploid extremophiles (including Thellungiella spp.).…”
Section: Stress Adaptation By Gene Duplicationmentioning
confidence: 99%